Antecedents Of Brand Origin Recognition Accuracy (BORA) And It’s Impact On Product Preferences Among Young Malaysians - Teo , Poh Chuin (2011)

(untitled)
This study seeks to examine the antecedents of Brand Origin Recognition Accuracy (hereinafter called BORA) score, measure young Malaysians’ BORA score and test the consequences of BORA score. The antecedents of BORA score are consumer ethnocentrism, consumer animosity, need for cognition, education, international experience, vocation and gender. In this study, there are six measures of BORA scores, namely Overall BORA score, Malaysia BORA score, Foreign BORA score, US BORA score, Europe BORA score and Singapore BORA score.